The Inquisition Tribunal in Goa: why and for what purpose? - Paiva, José (2017)
This article aims to explain the process which led to the founding of the Inquisition tribunal in Goa, the first Holy Office tribunal to be created outside Europe. Following a review of previous historiographical studies which have analyzed this question, it examines the mechanisms for Christianization/confessionalization deployed by the Iberian monarchs in Asia and America from a global and comparative perspective, based on a rereading and reinterpretation of Inquisition documents and correspondence from various agents who were involved in the process. It presents an explanation that emphasizes the existence of a cluster of causalities which created a dense network of convergent forces that favored the founding of an Inquisition tribunal in Asia in 1560.